2020
DOI: 10.1016/j.arth.2020.06.025
|View full text |Cite
|
Sign up to set email alerts
|

More Severe Radiographic Osteoarthritis Is Associated With Increased Improvement in Patients’ Health State Following a Total Knee Arthroplasty

Abstract: Background: To assess whether preoperative radiological severity of osteoarthritis (OA) is related to the level of improvement in patients' health state measured 1 year after total knee arthroplasty (TKA). Methods: Radiographic severity of OA was graded using the Kellgren-Lawrence (KL) classification. Two independent observers were blinded to patients' outcome scores. Health-related quality of life was measured using EQ-5D-3L preoperatively and at 12-month follow-up. The 5 dimensions of the EQ-5D were converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The positive correlation of pain indices and DN4 scores with PainDETECT, HADS depression/anxiety, and BPI pain severity variables, as observed in our study, indicates the association of neuropathic pain symptoms with pain intensity in the preoperative time, and it has also been suggested previously [ 13 ]. Our observation of slightly higher BPI pain severity prior to surgery in patients who were satisfied with the surgery is supported by previous observations indicating that patients with severe OA have significantly more improvement in their usual activities and pain after knee surgery than patients with less severe OA [ 42 ].…”
Section: Discussionsupporting
confidence: 88%
“…The positive correlation of pain indices and DN4 scores with PainDETECT, HADS depression/anxiety, and BPI pain severity variables, as observed in our study, indicates the association of neuropathic pain symptoms with pain intensity in the preoperative time, and it has also been suggested previously [ 13 ]. Our observation of slightly higher BPI pain severity prior to surgery in patients who were satisfied with the surgery is supported by previous observations indicating that patients with severe OA have significantly more improvement in their usual activities and pain after knee surgery than patients with less severe OA [ 42 ].…”
Section: Discussionsupporting
confidence: 88%
“…Scott et al (2021) [ 50 ] also found no significant effects of the KL grade on HRQoL changes after TKR. In contrast, a study by Rehman et al (2020) [ 48 ] evaluated whether severe radiographic OA was related to improvements in HRQoL after TKR. The results indicated that patients with severe OA, especially KL grade 4, had more clinically meaningful improvement in their EQ-5D Index than patients with less severe OA [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…A Norwegian study concluded that TKA offers a greater improvement in health state to patients as the radiological severity of osteoarthritis increases, using the EQ-5D as the endpoint at 12 months post-surgery. 23 The severe ceiling effect demonstrated with the EQ-5D calls this conclusion into question, as when the most common score postoperatively is 1, patients with more severe arthritis have more to gain than patients whose preoperative scores are closer to the ceiling.…”
Section: Discussionmentioning
confidence: 99%